2000
DOI: 10.1037/0003-066x.55.7.740
|View full text |Cite
|
Sign up to set email alerts
|

Responses to nervous breakdowns in America over a 40-year period: Mental health policy implications.

Abstract: in extending their original survey to a partial 40-year follow-up. A special thanks to J. Scott Long for his gracious statistical guidance. Teresa Damush, Jaya Rao, and Morris Weinberger provided helpful comments on earlier versions of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(79 citation statements)
references
References 31 publications
3
74
0
2
Order By: Relevance
“…This assumption is also supported by Swindle (2000) who found that between 1957 and 1996, the proportion of people with mental health problems in the US turning to informal support from social networks rose from 7% in 1957 to 28% in 1996. In Norway there seems to be a real change in the help seeking pattern with more people seeking different alternatives to traditional services (SSB 2008) 10 .…”
Section: Sum Of Experiences That Helpedmentioning
confidence: 72%
“…This assumption is also supported by Swindle (2000) who found that between 1957 and 1996, the proportion of people with mental health problems in the US turning to informal support from social networks rose from 7% in 1957 to 28% in 1996. In Norway there seems to be a real change in the help seeking pattern with more people seeking different alternatives to traditional services (SSB 2008) 10 .…”
Section: Sum Of Experiences That Helpedmentioning
confidence: 72%
“…For example, one possible scenario underlying our main result is that persons who initially seek treatment from master's level therapists or psychologists have an underlying latent (to the researcher) predisposition not to follow through with treatment subsequently. The predisposed patient we have in mind is drawn to a non-medical provider in 19 order to find out about treatment but then decides against it or seeks follow-up care through selfhelp groups or pastoral counseling (Swindle et al 2000). Another possibility for the relatively high incidence of treatment among medical providers is data construction.…”
Section: Discussionmentioning
confidence: 99%
“…Care differences can also be partly determined by the preferences of patients, who choose providers based on the types of care they offer. Based on the limited existing literature, it appears that patients' preferences are more likely to affect the decision to seek any care rather than the type of care (Frank and Kamlet 1989;Ettner and Herman 1997;Fortney, Rost, and Zhang 1998;Swindle et al 2000). So, patient demographic factors, such as age, gender, health, and mental health status have not been found to predict well the choice of particular provider specialties.…”
Section: Brief Review Of Provider Specialty In Mental Health Carementioning
confidence: 99%
See 1 more Smart Citation
“…It may also point to strategies for recovery. Nevertheless, a potential problem associated with belonging to this group is that there are stereotyped beliefs attached to severe mental illness (Martin et al, 2000;Swindle et al, 2000). Categorically referred to as stigma, these beliefs are spread across all levels of society and include expectations of violent and disorderly behavior as well as the conviction that persons with schizophrenia cannot work or make informed decisions about their welfare (Link et al, 1999;Phelan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%